Placebo-Controlled Trials in the Management of Crohn’s Disease: An Umbrella Review of Meta-Analyses - Richard Silva; José Nunes de Azevedo; Jorge Pereira Machado; Jorge Magalhães Rodrigues (Medical Sciences)
Introduction: Crohn’s disease is a chronic inflammatory bowel disease characterized by abdominal pain, diarrhea, and other symptoms. It can lead to significant complications and impact patients’ quality of life. Therefore, effective management strategies are essential for improving outcomes. Methods: To assess the efficacy of the treatments for Crohn’s disease, this umbrella review systematically addresses systematic reviews and meta-analyses on Crohn’s disease management published between 2013 and 2023. The quality of the included studies was assessed using the National Institutes of Health’s quality assessment tool. Results: Sixteen studies were included, evaluating various interventions for the induction and maintenance of remission. These included biologic agents (anti-TNF agents, anti-IL-12/23p40 antibodies, and integrin receptor antagonists), antimetabolites, and corticosteroids. Conclusions: The findings suggest that biologic agents may be promising options for both the induction and maintenance of remission in Crohn’s disease. Antimetabolites and corticosteroids may be effective in certain cases, but their efficacy and safety profiles require further investigation. The included studies varied in quality and sample size. More research is needed to confirm the findings and establish optimal treatment strategies. Moreover, while biologic agents show promise, the optimal management of Crohn’s disease requires further research. A personalized approach considering patient factors and disease characteristics is crucial for optimizing outcomes.